2016
DOI: 10.1186/s12870-016-0818-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genetic diversity and structure across a wide range of germplasm reveals prominent gene flow in apple at the European level

Abstract: BackgroundThe amount and structure of genetic diversity in dessert apple germplasm conserved at a European level is mostly unknown, since all diversity studies conducted in Europe until now have been performed on regional or national collections. Here, we applied a common set of 16 SSR markers to genotype more than 2,400 accessions across 14 collections representing three broad European geographic regions (North + East, West and South) with the aim to analyze the extent, distribution and structure of variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
124
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(138 citation statements)
references
References 68 publications
12
124
2
Order By: Relevance
“…For example, expected heterozygosity ( H E ) in ferals was 0.801, similar to our reference set of commercial cultivars ( H E = 0.807), which are largely self‐incompatible and outcrossing. The high heterozygosity in feral populations is also comparable to values observed in other studies on genetic diversity in apple collections such as Urrestarazu et al (), Urrestarazu et al () ( H E = 0.82), Liang et al () ( H E = 0.81), and Lassois et al () ( H E = 0.82). In contrast, the feral trees have much higher heterozygosity values than woody species such as Rubus occidentalis and Pinus resinosa , both self‐pollinating species, which display much lower levels of heterozygosity ( H E = 0.53 and H E = 0.508, respectively; Boys, Cherry, & Dayanandan, ; Dossett, Bassil, Lewers, & Finn, ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For example, expected heterozygosity ( H E ) in ferals was 0.801, similar to our reference set of commercial cultivars ( H E = 0.807), which are largely self‐incompatible and outcrossing. The high heterozygosity in feral populations is also comparable to values observed in other studies on genetic diversity in apple collections such as Urrestarazu et al (), Urrestarazu et al () ( H E = 0.82), Liang et al () ( H E = 0.81), and Lassois et al () ( H E = 0.82). In contrast, the feral trees have much higher heterozygosity values than woody species such as Rubus occidentalis and Pinus resinosa , both self‐pollinating species, which display much lower levels of heterozygosity ( H E = 0.53 and H E = 0.508, respectively; Boys, Cherry, & Dayanandan, ; Dossett, Bassil, Lewers, & Finn, ).…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have found genetic substructure within apple cultivars (Liang et al, ; Urrestarazu et al, ). Liang et al () observed two major groupings of 192 Italian apple cultivars, each with two subgroups.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The genetic diversity of fruit trees is nowadays assessed using DNA-based molecular markers [7][8][9][10][11][12] and the Portuguese Pyrus diversity has already been studied using RAPDs [13], AFLPs [14] and microsatellites-SSRs [15]. SSRs have become markers of choice because they are highly informative, reliable, and easy to use for cultivar identification thereby improving the management of collections by enabling the identification of duplicates, synonymies, and homonymies [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have for instance showed the 473 impact of genetic structure on genomic prediction, demonstrating that taking genetic structure 474 into account can improve GS efficiency (Guo et al, 2014;Isidro et al, 2015;Rio et al, 475 2019). Although in apple the genetic structure is known to be weak, with substantial levels of 476 admixture in apple cultivars (Urrestarazu et al, 2016;Vanderzande et al, 2017;Cornille et 477 al., 2019), it could still have a relevant effect on predictions, depending on the population 478 composition and the trait under investigation. Significant genetic structure has been identified, 479 for instance, between dessert and cider apples, which could potentially be correlated with fruit 480 quality traits (Lassois et al, 2016).…”
Section: Impact Of Genetic Clustering and Relatedness On Prediction Amentioning
confidence: 99%